Respuesta :

Answer:

[tex]\displaystyle \frac{3x+4}{(x-5)(x-1)} = \frac{19}{4(x-5)} +\frac{-7}{4(x-1)}[/tex]

Step-by-step explanation:

We are given the rational expression:

[tex]\displaystyle \frac{3x+4}{x^2 -6x +5}[/tex]

And we want to find two rational expressions that sum to the above expression.

This technique is known as partial fraction decomposition. First, factor the denominator into linear factors:

[tex]\displaystyle = \frac{3x+4}{(x-5)(x-1)}[/tex]

Let A and B be two unknown constants. We can let:

[tex]\displaystyle \frac{3x+4}{(x-5)(x-1)} = \frac{A}{x-5} + \frac{B}{x-1}[/tex]

Find A and B. Multiply the entire equation by the denominator:

[tex]\displaystyle \displaystyle \frac{3x+4}{(x-5)(x-1)}\left((x-5)(x-1)\right) = \left(\frac{A}{x-5} + \frac{B}{x-1}\right)\left( (x-5)(x-1)\right)[/tex]

Simplify:

[tex]3x + 4 = A(x-1) + B(x-5)[/tex]

To find A and B, let x equal some value such that it will cancel out one variable. First, let x = 1. Then:

[tex]\displaystyle 3(1) + 4 = A((1) - 1) + B((1) -5)[/tex]

Simplify:

[tex]\displaystyle 7 = A(0) + B(-4) \Rightarrow -4B = 7[/tex]

Hence:

[tex]\displaystyle B = -\frac{7}{4}[/tex]

To find A, let x = 5 (we choose this value because it allows us to cancel B):

[tex]\displaystyle 3(5) + 4 = A((5)-1) + B((5) - 5)[/tex]

Simplify:

[tex]\displaystyle 19 = A(4) + B(0) \Rightarrow A = \frac{19}{4}[/tex]

We had:

[tex]\displaystyle \frac{3x+4}{(x-5)(x-1)} = \frac{A}{x-5} + \frac{B}{x-1}[/tex]

Substitute:

[tex]\displaystyle \frac{3x+4}{(x-5)(x-1)} = \frac{\dfrac{19}{4}}{x-5} +\frac{-\dfrac{7}{4}}{x-1}[/tex]

In conclusion:

[tex]\displaystyle \frac{3x+4}{(x-5)(x-1)} = \frac{19}{4(x-5)} +\frac{-7}{4(x-1)}[/tex]